The Path to AI Arms Control: America and China Must Work Together to Avoid Catastrophe - Assoc. Prof. Ali Abdel Khader Mohamed Mamouri (The college of law and political science journal, 2024)
Henry A. Kissinger and Graham Allison wrote an article on October 13, 2023 in Foreign Affairs magazine, talking about the importance of artificial intelligence and its development in international relations, and the need to limit the spread of this type of smart weapons outside the control of superpowers, especially the United States and China